Anti-inflammatory therapy with tumour necrosis factor alpha inhibitors improves high-density lipoprotein cholesterol antioxidative capacity in rheumatoid arthritis patients. Issue 6 (17th July 2008) - Popa, C; van Tits, L J H; Barrera, P; Lemmers, H L M; van den Hoogen, F H J; van Riel, P L C M; Radstake, T R D J; Netea, M G; Roest, M; Stalenhoef, A F H
Abstract : Objective: High-density lipoprotein (HDL) antiatherogenic functions seem to be diminished during inflammatory conditions such as rheumatoid arthritis (RA). The aim of this study was to investigate the effects of tumour necrosis factor (TNF) inhibition on the antioxidative capacity of HDL in RA. Methods: Plasma lipids and paraoxonase (PON-1) activity were investigated in 45 RA patients, before and during 6 months of anti-TNF therapy. In addition, HDL was isolated and tested for its ability to inhibit copper-induced oxidation of low-density lipoprotein in vitro. Results: Plasma HDL concentrations did not change considerably after 6 months of therapy. However, stable increases of PON-1 activities were observed throughout the same period (p<0.03). The increases were more obvious when related to HDL or apolipoprotein AI concentrations. HDL total antioxidative capacity significantly improved 6 months after the initiation of anti-TNF therapy (p = 0.015). The initial improvement of PON-1 activity paralleled a decrease in the inflammatory status, whereas specific TNF blockade was likely to be responsible for the long-term effects. Conclusions: Anti-TNF therapy with infliximab has beneficial effects on lipids through changes in HDL antioxidative capacity, which might be clinically relevant and contribute to the reported protective effect of anti-TNF on cardiovascular morbidity in RA. This emphasises the importance of HDL antiatherogenic capacity for cardiovascular risk in chronic inflammatory conditions.